2009
DOI: 10.1007/s00038-009-0075-1
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and its association with health-relevant actions: investigating the role of time perspective with German census data

Abstract: Objective In this study, we seek to explain how unemployment is related to an increase in healthdamaging actions. A short time perspective, that is an orientation towards the present rather than the future, is hypothesised to account for this effect. The concept of time perspective is located within an action theoretical framework and the hypothesis is tested empirically. Methods We investigated the unemployed people's smoking behaviour and body-mass index (BMI) using German Microcensus data from 2003. Data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
4
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 34 publications
0
22
4
1
Order By: Relevance
“…[9] In addition, medical studies have found that stress increases both eating and smoking. [31][32][33][34] Moreover, job loss affects health behavior through an income effect.…”
Section: Discussionmentioning
confidence: 99%
“…[9] In addition, medical studies have found that stress increases both eating and smoking. [31][32][33][34] Moreover, job loss affects health behavior through an income effect.…”
Section: Discussionmentioning
confidence: 99%
“…Nossos resultados corroboram os estudos que mostram o desemprego positivamente associado ao tabagismo 23,24 , associação que se torna ainda mais intensa quanto maior a duração de desemprego 25 . Ao estudar trajetórias no mercado de trabalho (emprego estável até desemprego de longa duração) e mudanças na situação de fumante/não fumante ao longo de cinco anos, Virtanem et al 26 verificaram que os homens que se encontravam desempregados na linha de base e no seguimento fumavam mais cigarros/dia do que os que trabalhavam.…”
Section: Discussionunclassified
“…This must be seen in the context of the considerable psychosocial burden to which the unemployed are exposed. There are differences, for example, in health awareness, sporting activities and substance consumption (Hollederer 2011, RKI 2003, Schunck, Rogge 2010. Figure 5 shows the percentage of smokers and heavy smokers among men and women according to their employment status.…”
Section: How Geda 2010 Measures Unemployment and Precarious Employmentmentioning
confidence: 99%